Usability Testing and Evaluation of Texas Tech Sorghum Research Initiative Website - Kori Dunn; Cindy Akers; Corey Duysen; Courtney Meyers; Todd Chambers (Journal of Applied Communications, 2013)
Usability encompasses how easy something is to use. Usability testing is an integral part of user-centered design. The tests may be performed in a variety of ways including using a usability laboratory, a mixed-method data collection approach, and testing representative and non-representative users. Conducting usability tests on websites allows the site’s developers to observe users’ interaction with the site. If a website is not usable, users will go somewhere else to find the information they are looking for and the purpose of the site is lost when this happens. The efficiency, error, learnability, and satisfaction of a representative and non-representative user groups were measured during a usability test of the Texas Tech SRI site that employed mixed-method data collection. The users were given a series of tasks to perform that related to the site’s navigational scheme, layout, and content. The representative and non-representative groups efficiently navigated the site and were able to repeatedly utilize the site’s functions. However, it was concluded that the representative user group committed less errors during their interaction with the site and that their overall satisfaction with the site was higher than the non-representative user group. Representative user groups may find a higher satisfaction level in this website than non-representative groups.
Keywords: MEELS; efficiency; website usability; learnability; satisfaction; sorghum; representative user group